Analysis of Postapproval Clinical Trials of Therapeutics Approved by the US Food and Drug Administration Without Clinical Postmarketing Requirements or Commitments - Skydel, Joshua J. (JAMA Netw Open, 2019)
IMPORTANCE: The US Food and Drug Administration (FDA) can use postmarketing requirements to mandate pharmaceutical companies to conduct clinical trials after the approval of novel therapeutics. Pharmaceutical companies can also agree to conduct nonmandated clinical trials as postmarketing commitments. However, when therapeutics are approved by the FDA without postmarketing requirements or postmarketing commitments, it is not well known how often pharmaceutical companies voluntarily conduct trials and report results monitoring safety or efficacy after approval. OBJECTIVE: To characterize postapproval clinical trials sponsored by pharmaceutical companies of therapeutics initially approved by the FDA without clinical postmarketing requirements or commitments. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional analysis included postapproval clinical trials conducted with at least 1 site in the United States sponsored by pharmaceutical companies of therapeutics first approved by the FDA from 2009 through 2012. Analyses were conducted June 11, 2018, to November 30, 2018. MAIN OUTCOMES AND MEASURES: Postapproval clinical trials registered on ClinicalTrials.gov generating safety or efficacy data, characteristics including whether trials focused on approved or unapproved indications, study design elements, and rates of study completion and results reporting. RESULTS: From 2009 through 2012, the FDA approved 110 novel therapeutics for 120 indications, of which 37 novel therapeutics for 39 indications did not have postmarketing requirements or commitments for new clinical studies at the time of first approval. For 31 therapeutics (83.8%), there were 600 postapproval clinical trials sponsored by pharmaceutical companies. Most trials investigated therapeutics for new indications (363 [60.5%]) or expanded populations of the originally indicated disease (122 [20.3%]). Trials were often small (median [interquartile range] enrollment, 44 [21-131] participants), nonrandomized (359 [59.8%]), unblinded (455 [75.8%]), and lacked comparators (381 [63.5%]). Approximately half of the trials (311 [51.8%]) assessed at least 1 clinical outcome. Of 300 terminated or completed trials, 204 trials (68.0%) had reported results on ClinicalTrials.gov a median (interquartile range) 16 (13-25) months after their primary completion date. For the 96 trials (32.0%) without reported results, a median (interquartile range) 35 (13-62) months had passed since their primary completion date. CONCLUSIONS AND RELEVANCE: Pharmaceutical companies frequently conducted clinical trials after approval, even when there were no clinical postmarketing requirements or commitments at approval. However, most of these trials evaluated new indications or expanded patient populations rather than monitored approved uses, and nearly half of the trials remained incomplete more than 5 years after original therapeutic approval.